Peranan Pembantu dan Anggota Rumahtangga Lain (Extended Family) Terhadap Partisipasi Kerja dan Lapangan Usaha Ibu Rumah Tangga Di Kota Jambi - Apriantoni Apriantoni; Wiyan Mailindra (Ekonomis: Journal of Economics and Business, 2021)
The purpose of this study was to determine the role of other household members "extended family" on the work participation and business field of housewives as well as taking into account other factors that play a role in increasing work participation and business preferences of housewives, including: level of education of housewives, per capita expenditure, presence of children aged 0-6 years and 7-12 years, age group, husband's education, and husband's working status. The analytical method that will be used in this research is descriptive analysis and inferential analysis. The analysis used in this paper uses a multifactorial logit regression model to see the ratio of the tendencies of the independent variables in influencing the work participation of housewives. The results of this study indicate that the role of other household members is very helpful for housewives in work participation and business fields, both education, expenditure, and the presence of children aged 0-6 years and 7-12 years.